2023
DOI: 10.1186/s12939-023-01887-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic status and cognitive ability among Chinese older adults: the moderating role of social support

Abstract: Background Understanding the causes and pathways of cognitive decline among older populations is of great importance in China. This study aims to examine whether the discrepancy in socioeconomic status (SES) makes a difference to the cognitive ability among Chinese older adults, and to disentangle the moderating role of different types of social support in the process in which SES influences cognition. Methods We utilized a nationally representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
0
0
Order By: Relevance
“…In Taiwan, where IMPT is not covered by insurance, IMPT patients tend to have higher socioeconomic status. Higher socioeconomic status is associated with better cognitive function [39,40], explaining our study's findings. We had accounted for education level as a proxy for socioeconomic status to address this issue.…”
Section: Discussionsupporting
confidence: 69%
“…In Taiwan, where IMPT is not covered by insurance, IMPT patients tend to have higher socioeconomic status. Higher socioeconomic status is associated with better cognitive function [39,40], explaining our study's findings. We had accounted for education level as a proxy for socioeconomic status to address this issue.…”
Section: Discussionsupporting
confidence: 69%
“…The study by Lin et al reports that females with primary or lower education levels are closely linked to subjective cognition decline symptoms. A hypothesis is that people with a good educational level have a higher brain capacity than people with a lower educational level, which gives them the advantage of slowing cognitive decline [ 22 ]. On the other hand, the fact that women are more likely to present a higher probability has also been related to the fact that women are more concerned about their state of health and have a greater perception of changes or the progression of symptoms [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also observed in a study by Liu et al, in which elderly people with widowed/separated marital status were more susceptible to cognitive impairment and performed poorly in all domains of cognition [ 59 ]. On the other hand, the study by Shi et al also reported that older people who had a disadvantaged socio-economic status were more likely to develop a lower level of cognitive ability in later life after controlling the results for age, sex, marital status, living region, health insurance, lifestyle factors, and physical health status [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations